Deriving three-dimensional bosonization and the duality web - Nastase, Horatiu [UNESP]; Núñez, Carlos (Elsevier, 2018)
Recently, a duality web for three dimensional theories with Chern–Simons terms was proposed. This can be derived from a single bosonization type duality, for which various supporting arguments (but not a proof) were given. Here we explicitly derive this bosonization, in the Abelian case and for a particular regime of parameters. To do this, we use the particle-vortex duality in combination with a Buscher-like duality (both considered in the regime of low energies). As a corollary, Son's conjectured duality is derived in a somewhat singular limit of vanishing mass.